THE APPLICABILITY OF DOMESTIC LAW IN INTERNATIONAL BUSINESS CONTRACTS: A STUDY ON INDONESIAN COURTS' CASES - Bintang, Sanusi (Kanun Jurnal Ilmu Hukum, 2024)
This article explores the application of domestic law and forum selection clauses in international business contracts within Indonesian legal system. It provides an analysis of the legal reasoning behind two significant court cases: Beauchamp Guerin v. Gunarsa and AXN v. Karyamegah. Utilizing a normative legal research methodology, the study examines these cases alongside relevant statutes, adopting a case-based approach rather than a strictly statutory one. The selected cases were chosen for their relevance to the intersection of international business contracts and domestic law, particularly in relation to forum selection clauses. The analysis is grounded in legal reasoning, demonstrating that the principles of choice of law and choice of forum support the applicability of domestic law and forum selection clauses in international business contracts, bolstered by Indonesian contract law. In Beauchamp Guerin v. Gunarsa, the court upheld the domestic law by affirming the validity of the contract and recognizing issues of nonperformance and damages in accordance with Indonesian law. Similarly, in AXN v. Karyamegah, the court asserted its jurisdiction over the case, finding grounds for nonperformance and damages as well. The findings presented in this article are significant for Indonesia, particularly in light of the absence of specific legislation governing international business contracts. Thus, this research serves both theoretical and practical purposes, filling a gap in existing literature that has predominantly focused on the application of foreign national laws and forums while overlooking the importance of domestic legal frameworks.